Wirelessly teleoperated differential wheeled chassis of the robot on the ESP32-WROOM-32 MCU module - Ponzoni, Rafael Leal; Boas, Ana Sophia Cavalcanti Alves Vilas; Monteiro, Vinícius Emídio; Fernandes, Daniel de Almeida (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
This paper presents an experimental, ESP32-WROOM-32 MCU based, differential mobile robot for teaching robotics to undergraduate students. The main idea is for students to solidify their knowledge in control theory, system identification, path planning, and Internet of Things through practical activities, thus enabling them to apply these skills in the industrial job market. Experimental results conducted with a prototype are included to demonstrate the effectiveness of the work.